Female infidelity as a result of domestic violence - Romero, Holguer (2017)
Introduction: Infidelity is the product of breaking couple agreements. Family violence causes psychological symptoms that impact the woman’s affective behavior and cause collateral effects in the family. Objective: To determine the causes that produce infidelity in battered women. Design: Mixed design study of process integration, sequential exploratory, derivative type. Setting: Judiciary Council, Santa Elena, Ecuador. Participants: 220 women who reported aggression by their partner. Interventions: From February to December 2015, in-depth interviews were applied, and with this data the quantitative instrument was developed and validated by judges and experts. Main outcome measures: Infidelity at home, and infidelity at work. Results: Two categories were identified: infidelity at home, and infidelity at work. The symptomatology determining the causes for women being unfaithful on each context was obtained. 43% of women had a male friend to share life with, 20% were sexually dissatisfied, 71% reported that their sexual relations were boring, and 29% were unfaithful in order to maintain their social economical condition. Conclusions: For women, the violence context produced emotional vulnerability that induced them to find compensation through diverse illusions conducing to infidelity; even so, they remained with their partner to keep personal and familiar welfare.